2018
DOI: 10.5194/tc-12-2461-2018
|View full text |Cite
|
Sign up to set email alerts
|

Glacier change along West Antarctica's Marie Byrd Land Sector and links to inter-decadal atmosphere–ocean variability

Abstract: Abstract. Over the past 20 years satellite remote sensing has captured significant downwasting of glaciers that drain

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 95 publications
1
34
1
Order By: Relevance
“…Besides the fast-changing Amundsen Sea Sector, the Bellingshausen Sea Sector at Abbot Ice Shelf is less studied but also vulnerable to CDW forcing (Christie et al, 2016). Just recently, the velocity at the grounding line increased (+20 %, 2007-2014), a dynamic thinning signal evolved which is related to ice dynamics and lower snowfall (Chuter et al, 2017), and minor grounding line retreat has occurred (Christie et al, 2016). The recent dynamic thinning signal observed by Chuter et al (2017) is in line with the glacier front retreat at Abbot Ice Shelf observed since the second decade, where westerlies increased by +0.24 m/s from the first to the second decade, indicating vulnerability to upwelling CDW.…”
Section: West Antarcticamentioning
confidence: 99%
“…Besides the fast-changing Amundsen Sea Sector, the Bellingshausen Sea Sector at Abbot Ice Shelf is less studied but also vulnerable to CDW forcing (Christie et al, 2016). Just recently, the velocity at the grounding line increased (+20 %, 2007-2014), a dynamic thinning signal evolved which is related to ice dynamics and lower snowfall (Chuter et al, 2017), and minor grounding line retreat has occurred (Christie et al, 2016). The recent dynamic thinning signal observed by Chuter et al (2017) is in line with the glacier front retreat at Abbot Ice Shelf observed since the second decade, where westerlies increased by +0.24 m/s from the first to the second decade, indicating vulnerability to upwelling CDW.…”
Section: West Antarcticamentioning
confidence: 99%
“…Projections of 21st century Antarctic ice sheet evolution, however, vary widely, with projected upper bounds ranging from 30 cm of sea level equivalent (Ritz et al, 2015) to over 1 m (DeConto and Pollard, 2016), depending on model characteristics and physical processes, as well as the climate scenarios adopted. Previous efforts from the ice sheet modeling community for the IPCC-AR5 (Intergovernmental Panel for Climate Change Fifth Assessment Report; Church et al, 2013) tried to estimate the ice sheet evolution under several climate scenarios (Bindschadler et al, 2013;Nowicki et al, 2013a, b). These results had a large spread for all scenarios, as a consequence of differences in model characteristics and processes included, initialization methods, and the interpretation and application of model forcings (Nowicki et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…While grounding line retreat has been observed since 2003 (ref. 24 ), the ice shelf is anchored at its seaward margin by eight large islands and over 23 pinning points which stabilise the ice shelf calving front, resulting in a relatively small area change over the past three decades 25 , 26 . Despite the absence of significant area change, strong ice shelf thinning (−16.1 m/decade) has been observed since the 1990s 27 , producing one of the largest sources of fresh water input to the Southern Ocean 28 , more than double that of the neighbouring Amundsen Sea ice shelves 29 .…”
Section: Introductionmentioning
confidence: 99%